Effect of Beauveria bassiana (Hypocreales: Clavicipitaceae) and Fungicide Applications on Megacopta cribraria (Hemiptera: Plataspidae) in Soybean. Issue 1 (23rd August 2017) - Knight, Ian A.; Roberts, Phillip M.; Gardner, Wayne A.; Oliver, Kerry M.; Jacobson, Alana; Toews, Michael D.
Abstract : Core Idea: Routine fungicide applications to soybean did not consistently affect kudzu bug suppression by Beauveria bassiana. Declining populations of kudzu bug, Megacopta cribraria (F.), in the southeastern United States have been observed since 2013 and are generally attributed to increased prevalence of natural enemies. Beauveria bassiana (Bals.‐Criv.) Vuill. infects kudzu bugs in North America, but the level of pest suppression has not been reported. Beauveria bassiana is sensitive to classes of fungicides used to manage foliar pathogens in soybean. Here, the degree to which B. bassiana suppressed kudzu bugs in soybean and changes in pest abundance as a result of routine fungicide applications were assessed in soybean plots located in Alabama and Georgia. In Alabama, seed and foliar treatments of B. bassiana spores and treatment with fungicides were tested. In Georgia, conservation tillage and fungicide applications were tested for their effect on kudzu bug populations and B. bassiana related mortality. Kudzu bug suppression due to Beauveria differed between sites, with 20 to 75% cadavers to total bugs observed in Alabama and 1 to 6% observed in Georgia. Tillage had no effect on kudzu bug numbers or suppression, though fungicide applications decreased suppression compared with the non‐treated control on one sample date. Beauveria bassiana seed and foliar treatments did not affect kudzu bug suppression. Effects of fungicides on ratios of cadavers to total bugs were variable, though less Beauveria was observed in plots receiving a fungicide tank mix compared with non‐treated controls. Fungicides had no consistent effect on kudzu bug populations at either site.